2010
DOI: 10.1021/jf103989j
|View full text |Cite
|
Sign up to set email alerts
|

Hemisynthesis of Dihydroumbellulols from Umbellulone: New Cooling Compounds

Abstract: Although menthol is a common ingredient used in food products, other molecules also evoke coolness through stimulation of the somatosensory system. To discover new molecules having cooling properties, we virtually screened the chemical structures of terpenes and sesquiterpenes to find structures that are similar to (-)-menthol. We realized that dihydroumbellulols could be good candidates. Although their occurrence was reported in Hyptis pectinata Poit, we were unable to obtain these molecules from the plant or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…When assayed for TRPM8 activation, UMB showed only modest potency, but the activity increased in its reduced analogs, in accordance with the recent identification of derivatives of umbellulol as potent coolant agents [28]. The reduced analogs are devoid of the offensive trait of the natural product that seems entirely related to activation of TRPA1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…When assayed for TRPM8 activation, UMB showed only modest potency, but the activity increased in its reduced analogs, in accordance with the recent identification of derivatives of umbellulol as potent coolant agents [28]. The reduced analogs are devoid of the offensive trait of the natural product that seems entirely related to activation of TRPA1.…”
Section: Discussionsupporting
confidence: 58%
“…Chemical modification of umbellulone Compounds 3a,b, 4a, and 5 were prepared from umbellulone as described in the literature [10,28]. Acetyl tetrahydroumbellulone [4b] was prepared by acetylation of tetrahydroumbellulone, and its spectroscopic characterization will be reported in a future comprehensive paper on the chemistry of umbellulone.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity over time is a very important parameter, the objective of the sensory evaluations being first to confirm the cooling effect of the dihydroumbellulol (18), and then to compare its performance with that of (-)-menthol. [49] Thirty trained panelists evaluated the perceived cooling intensity over time of the two samples, dihydroumbellulol and (-)-menthol (one sample per session, at 50 mg/L). Each subject received a sample (30 mL) in a cup and was asked to taste it and to start a timer at the same time.…”
Section: Investigations Of the Pungent Effects Of Some Botanicalsmentioning
confidence: 99%
“…The I max values showed that dihydroumbellulol is weaker than (-)-menthol (significant difference for I max ) and its persistent trigeminal effect is shorter, with a more pronounced delay. [49]…”
Section: -Methylbicyclo[310]hex-3-en-2-olmentioning
confidence: 99%